Sudden Death Induced by Acute Inhalation of Aerosolized Carfentanil - Gao, Xiuping; Zhuang, Jianguo; Chen, Zikuan; Shi, Shan; Xu, Fadi (Archives of Clinical and Biomedical Research, 2025)
Inhalation of carfentanil (CRF) aerosol could rapidly induce death in humans and CRF aerosol exposure induces respiratory depression in animals; however, the dynamic progression of cardiorespiratory failure leading to sudden death induced by acute CRF aerosol exposure remains unclear. This study aimed to establish a rat model that allows dynamically characterizing the cardiorespiratory failure prior to death following acute exposure to a lethal concentration of CRF aerosol. Two groups of anesthetized and spontaneously breathing rats were exposed to aerosolized vehicle and CRF (4 mg/m3) for 10 minutes respectively. CRF exposure resulted in 100% mortality among the tested rats. The cardiorespiratory responses were characterized sequentially by: immediate ventilatory depression resulting from rapidly developed bradypnea, persistent ventilatory depression, and significant irregularities in both breathing (ataxic breathing) and heart beat rhythms that ultimately caused ventilatory and cardiac arrest at 7.7 ± 0.6 and 9.0 ± 0.7 minutes-, after the onset of CRF exposure. Our results establish a rat model of cardiorespiratory failure and sudden death resulted from acute exposure to CRF aerosol. This model may facilitate further investigation into the mechanisms underlying cardiorespiratory failure and the development of potential countermeasures.